Relationship Between Knowledge, Attitude and Motivation of Officers in Managing the COVID-19 Vaccine Cold Chain: A Systematic Review - Sudarto Edi Hartono; Solikhah Solikhah; Sulistyawati Sulistyawati (Epidemiology and Society Health Review (ESHR), 2023)
Background: Vaccines are an important tool in preventing serious infectious diseases. Cold chain management is essential to maintain vaccine quality, including storage, transportation, and distribution at appropriate temperatures. This study aims to investigate the relationship between knowledge, attitudes, and motivation of health workers responsible for cold chain management of the COVID-19 vaccine. Method: This was a systematic literature review study by searching through databases: Google Scholar, PubMed, Semantic Scholar, and Frontiers, using some keywords. 76 relevant previous studies were found. After filtering for publication year (post-2019), they reviewed 19 articles' abstracts. However, 10 articles lacked information on vaccine officers' knowledge, attitudes, and motivation in cold chain management. Thus, only 9 articles were included in the review. Results: The results show that adequate knowledge, training, and understanding of guidelines significantly influence desired vaccine cold chain management practices. These studies also highlight the importance of understanding guidelines, efficient implementation, and sustainability aspects in vaccine management. Conclusion: This research concludes that to increase the effectiveness of vaccination programs, efforts are needed to increase knowledge, training, and implementation of guidelines among health workers responsible for the vaccine cold chain. Efforts to understand and implement sustainable practices are also crucial. The conclusions from this research can help decision-makers improve vaccine cold chain management to ensure the success of the vaccination program.